2021
DOI: 10.1080/13814788.2021.1985997
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and economic burden of frequent attenders with medically unexplained symptoms in primary care in Israel

Abstract: Background Frequent Attenders with Medically Unexplained Symptoms (FA/MUS) are common in primary care, though challenging to identify and treat. Objectives This study sought to compare FA/MUS to FA with organic illnesses (FA/OI) and the general clinic population (Non-FA) to understand their demographic characteristics and healthcare utilisation patterns. Methods For this retrospective, observational study, Electronic Medical Records (EMR) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Frequent attenders (FAs) are a unique patient group characterised by the consumption of a disproportionate number of medical consultations and a high number of visits per year to primary care physicians (PCP) (Hodgson et al, 2005). FAs are defined in the literature by the number of physician visits per year (usually 6–12) (Scaife et al, 2000) or by the top percentage (usually 3–10%) of attenders during a single year (Hammerman et al, 2021; Neal et al, 1998; Pymont & Butterworth, 2015; Reho et al, 2018; Vedsted & Christensen, 2005). Several studies have shown that about 10–30% of FAs continue to seek frequent consultation for more than one year (Carney et al, 2001; Smits, Brouwer, van Weert, et al, 2009), and they are often defined as persistent FAs (Smits et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Frequent attenders (FAs) are a unique patient group characterised by the consumption of a disproportionate number of medical consultations and a high number of visits per year to primary care physicians (PCP) (Hodgson et al, 2005). FAs are defined in the literature by the number of physician visits per year (usually 6–12) (Scaife et al, 2000) or by the top percentage (usually 3–10%) of attenders during a single year (Hammerman et al, 2021; Neal et al, 1998; Pymont & Butterworth, 2015; Reho et al, 2018; Vedsted & Christensen, 2005). Several studies have shown that about 10–30% of FAs continue to seek frequent consultation for more than one year (Carney et al, 2001; Smits, Brouwer, van Weert, et al, 2009), and they are often defined as persistent FAs (Smits et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…FAs often have complex health problems (Bergh et al, 2007; Reho et al, 2019) that manifest in a greater rate of diagnoses and chronic diseases compared to other health consumers (Vedsted & Christensen, 2005), as well as psychiatric and psychological symptomatology, impairment in activities of daily living (Pymont & Butterworth, 2015), worse self‐rated health, lower physical functioning and physical illnesses (Hajek et al, 2021), lower quality of life (Kivela et al, 2018) and lower ability to cope with life events (Bergh et al, 2006). Hammerman et al (2021) have found that almost 50% of FAs have medically unexplained symptoms. Socioeconomic deprivation has also been suggested as a characteristic of FAs (Scaife et al, 2000) as well as lower age and unemployment (Hajek et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation